EFFICIENCY OF PRODUCTION FACTORS USAGE IN ENVIRONMENTALLY CONSCIOUS POTATO FARMING IN KARANGREJA DISTRICT, PURBALINGGA REGENCY - Ayu Sitanini; Victor Bintang Panunggul; Dwi Kurniawati; Raflina Nurwanda Ningsih (Universitas Perjuangan Tasikmalaya, 2024)
The main problem in potato farming is the problem of efficient use of production factors. Efficient use of production factors will determine the size of profits. National-level potato productivity is decreasing from year to year. National-level potato productivity in 2023 will be 19.27 tons/ha. Potato productivity in Karangreja District is 14,715 tonnes/ha, below the national average. The research aimed to describe the environmental conditions in the area due to potato crops and analyze the influence of product factors on productivity and price/allocative efficiency in potato farming in Karangreja District, Purbalingga Regency. The research method used is a survey, which uses simple cluster sampling. The analysis method uses financial analysis methods, and multiple linear regression analysis (Cobb Douglas production function). Seeds, manure, organic fertilizers, pesticides, and the area of land used cannot be increased to increase product per unit area. Physically, the workforce used can still be increased to improve the product. At the price level of potato products of IDR 8,000 and labor wages of IDR 40,000, the use of labor in potato farming in Karangreja District already provides maximum profits